2019
DOI: 10.1039/c9na00429g
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional stretchable sensors based on a 3D-rGO wrinkled microarchitecture

Abstract: A 3D-rGO wrinkled film with a graphene expansion structure and stretchable 3D-rGO bulge for application in multi-functional sensors is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In Figure 3f, we compare the gauge factor and workable sensing strain range of our strain sensor with those of the previously reported piezoresistive strain sensors with the surface buckling method. [22][23][24][25][26][27][28] The work of these peers falls into three categories including metals, carbon materials, and semiconductor materials such as ITO in this work. It is found that the ITObased strain sensor in this work exhibits the highest sensitivity of 610 compared to the reported sensors, and promotes the recording sensitivity of the same type of sensors nearly by one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 3f, we compare the gauge factor and workable sensing strain range of our strain sensor with those of the previously reported piezoresistive strain sensors with the surface buckling method. [22][23][24][25][26][27][28] The work of these peers falls into three categories including metals, carbon materials, and semiconductor materials such as ITO in this work. It is found that the ITObased strain sensor in this work exhibits the highest sensitivity of 610 compared to the reported sensors, and promotes the recording sensitivity of the same type of sensors nearly by one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, surface buckling has been explored to develop stretchable piezoresistive strain sensors with carbon or metal materials. [22][23][24][25][26][27][28] The sensitivity of these devices is mainly decided by the geometric effect since the resistivities of carbon or metal materials change little versus strain. Carbon-based strain sensors that are made of 2D materials exhibit the large stretchability due to the small mechanical strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The disappearing characteristic peaks of oxygen‐containing functional groups and the significantly decreased relative oxygen content on rGO film can exemplify (from Fourier transform infrared (FTIR) spectra and energy dispersive X‐ray mapping images of Figures S1,S2, Supporting Information) that the GO film has been well reduced. [ 32,33 ] In the next step, the pre‐stretched rGO substrate was applied as the receiver for the subsequent electrospinning process of ferric chloride (FeCl 3 )‐doped poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP) nanofiber film. After releasing the pre‐stress, a light yellow WNF with a large specific surface area was formed (Figure S3a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Also, because laser-reduced graphene is flexible, highly conductive, and green and non-toxic, it can be applied to the manufacture of human wearable smart sensors [31][32][33]. Although many graphene-based piezoresistive sensors have been reported [7,[34][35][36], there is still room for improvement in terms of sensitivity and linear range. Compared with the layered structure of pure graphene films, the graphene-based piezoresistance sensor with wrinkle [37], conical frustum-like [38], pyramid [39] and other microstructures [40,41] prepared by different methods always show better sensing performance.…”
Section: Introductionmentioning
confidence: 99%